Biomaterials-Mediated Regulation of Macrophage Cell Fate - Liu, Yining; Segura, Tatiana (Frontiers in Bioengineering and Biotechnology, 2020)
Endogenous regeneration aims to rebuild and reinstate tissue function through enlisting natural self-repairing processes. Promoting endogenous regeneration by reducing tissue-damaging inflammatory responses while reinforcing self-resolving inflammatory processes is gaining popularity. In this approach, the immune system is recruited as the principal player to deposit a pro-reparative matrix and secrete pro-reparative cytokines and growth factors. The natural wound healing cascade involves many immune system players (neutrophils, macrophages, T cells, B cells, etc.) that are likely to play important and indispensable roles in endogenous regeneration. These cells support both the innate and adaptive arms of the immune system and collectively orchestrate host responses to tissue damage. As the early responders during the innate immune response, macrophages have been studied for decades in the context of inflammatory and foreign body responses and were often considered a cell type to be avoided. The view on macrophages has evolved and it is now understood that macrophages should be directly engaged, and their phenotype modulated, to guide the timely transition of the immune response and reparative environment. One way to achieve this is to design immunomodulating biomaterials that can be placed where endogenous regeneration is desired and actively direct macrophage polarization. Upon encountering these biomaterials, macrophages are trained to perform more pro-regenerative roles and generate the appropriate environment for later stages of regeneration since they bridge the innate immune response and the adaptive immune response. This new design paradigm necessitates the understanding of how material design elicits differential macrophage phenotype activation. This review is focused on the macrophage-material interaction and how to engineer biomaterials to steer macrophage phenotypes for better tissue regeneration.